Pengetahuan dan Kecemasan pada Lansia terhadap COVID-19 - Loura Caroline Korengkeng; Cornelia Londok (Fakultas Ilmu Keperawatan Universitas Klabat, 2023)
The anxiety experienced by the elderly as cases of COVID-19 increase is related to knowledge, because good and correct knowledge needed to manage all the information. The aim of this study is to find out the relationship between the level of knowledge and the level of anxiety of the elderly about COVID-19 in Suwaan Village, North Minahasa. A cross-sectional study was conducted in May 2021 in which sampling technique used was a total sampling technique with a total of 51 respondents. The instrument used is a questionnaire scale of knowledge and anxiety levels of coronavirus. The results indicate that the level of knowledge of the respondents was in the moderate category with a total of 29 respondents (56.9%). While the anxiety level of the elderly was mostly in the severe category with a total of 42 respondents (82.4%). The data were analyzed using the SPSS and presented in the form of a frequency distribution table and Spearman's rho. It was found that there was no significance relationship between the level of knowledge and the level of anxiety in the elderly in Suwaan Village with p-value = 0.922. It is recommended that the government to actively giving health promotion about COVID-19 and for family members to play an active role in providing correct information, show attention physically, emotional support and psychological support to the elderly in reducing anxiety and to have good knowledge. Abstrak Kecemasan yang dialami lansia seiring meningkatnya kasus COVID-19 berkaitan dengan pengetahuan, karena diperlukan pengetahuan yang baik dan benar untuk mengelola semua informasi yang beredar. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara tingkat pengetahuan dan tingkat kecemasan lansia terhadap COVID-19 di Desa Suwaan, Minahasa Utara. Metode yang digunakan adalah korelasi deskriptif dengan pendekatan cross sectional, yang dilakukan pada bulan Mei 2021. Teknik pengambilan sampel menggunakan teknik total sampling dengan jumlah 51 responden. Instrumen yang digunakan adalah kuesioner skala tingkat pengetahuan dan tingkat kecemasan virus corona. Hasil penelitian didapati bahwa tingkat pengetahuan responden berada pada kategori cukup dengan jumlah 29 responden (56,9%). Sedangkan tingkat kecemasan lansia sebagian besar berada pada kategori berat dengan jumlah 42 responden (82,4%). Setelah dilakukan analisis data dan uji Spearman’s rho, ditemukan bahwa tidak terdapat hubungan yang signifikan antara tingkat pengetahuan dengan tingkat kecemasan pada lansia di Desa Suwaan dengan nilai p = 0,922. Direkomendasikan pemerintah setempat untuk mengadakan promosi kesehatan tentang COVID-19 dan anggota keluarga untuk berperan aktif dalam memberikan informasi yang benar, dukungan secara fisik, emosional dan psikologis kepada lansia agar dapat membantu lansia menurunkan tingkat kecemasan dan memiliki pengetahuan yang baik. Kata kunci : COVID-19, Kecemasan, Pengetahuan